A framework to utilize building information modeling (BIM) system for optimizing lighting in historic building in Malaysia - Loron, Mehrdad Sahraei (2014)
Unacceptable level of electricity consumption for lighting in historic buildings, mentioned by other experts in Malaysia, has been emphasized as a problem to be investigated for the current study. In this regard, the present research aims to specify the possibilities and limitations for conservation activities in historic buildings especially in terms of lighting components. It also attempts to specify the acceptable methods of utilizing the required tools and devices which support energy efficiency in historic building through reducing electricity consumption for lighting; and finally, the present research recommends the features and specifications of a Building Information Modeling (BIM) system which leads to the reduction of electricity consumption for lighting in historic buildings. Through literature review, firstly the study clarifies the research problem, main and sub-research questions, research objectives, theoretical framework, and theoretical proposition. Secondly, based on the findings through literature survey, qualitative case study research methodology is selected for this inquiry. Lastly, interviewing the experts with an in-depth semi-structured open-ended interview questionnaire is chosen as the suitable method of data collection. In order to achieve the aforementioned goals,two historic buildings which are currently operating as museums including (1) the Muzium Tekstil (National Textile Museum) in Kuala Lumpur; and (2) the Muzium Diraja Abu Bakar (Royal Abu Bakar Museum) in Johor, are selected as the units of analysis for starting the data collection process. In this respect, the findings related to the first objective indicate that despite the limitations for conserving historic buildings in external parts, internal changes through employing suitable methods and approaches are possible and acceptable. Regarding the second objective, findings reveal that a successful and energy efficient lighting system for historic buildings needs to have two essential factors including 1) installing energy efficient tools and devices and 2) applying suitable methods for installing lighting tools and devices to control any possible damages on historic buildings valuable characteristics. The findings concerning the third objective indicate that a lighting system for being successful in historic buildings needs to be intelligent and simple, provide feedback, consider daylight, consider different levels of heat and humidity inside the historic buildings, and investigate the levels of required illumination for reducing electricity waste. At the end, the study proposes a framework to utilize BIM system for optimizing lighting in historic buildings in Malaysia along with respecting their valuable characteristics.